TRANSFORMASI NILAI BHAKTI MARGA DALAM PELAYANAN SOSIAL BERBASIS KEARIFAN LOKAL - Arya Adnyana, I Wayan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study aims to examine the relevance and application of Bhakti Marga in the context ofsocial services and cultural preservation in the era of globalization. Modernization challenges haveshifted values and cultural identity within Hindu communities. Using a descriptive qualitativeapproach through library research and philosophical reflection, the study reveals that Bhakti Margais not only a spiritual path but also an ethical and practical foundation for cultivating service ethosand cultural awareness. Its teachings on love, selfless devotion, and respect for tradition inspireHindus to actively engage in social welfare and preserve sacred values. The research shows thatBhakti Marga can be reconstructed as a sustainable framework for spiritual-based social action.Thus, this study contributes theoretically to the development of Bhakti philosophy as a contextual andadaptive path of devotion, and offers practical approaches for Hindu youth to maintain culturalidentity and integrity amidst globalization.